2009
DOI: 10.1016/j.cub.2009.07.072
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-free Terminals of Rough ER Allow Formation of STIM1 Puncta and Segregation of STIM1 from IP3 Receptors

Abstract: SummaryStore-operated Ca2+ entry is a ubiquitous mechanism that prevents the depletion of endoplasmic reticulum (ER) calcium [1]. A reduction of ER calcium triggers translocation of STIM proteins, which serve as calcium sensors in the ER, to subplasmalemmal puncta where they interact with and activate Orai channels ([2–8]; reviewed in [9]). In pancreatic acinar cells, inositol 1,4,5-trisphosphate (IP3) receptors populate the apical part of the ER. Here, however, we observe that STIM1 translocates exclusively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
118
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 31 publications
(33 reference statements)
6
118
3
Order By: Relevance
“…The channels are activated and extracellular calcium is taken up from the extracelluar environment. This uptake sustains the elevated levels of intracellular calcium [34] . Importantly, it has been shown that a CRAC channel inhibitor, GSK-7975A, inhibited the calcium entry into acinar cells.…”
Section: Effects Of Ethanol On the Cellular Mobilization Of Calcium Amentioning
confidence: 88%
“…The channels are activated and extracellular calcium is taken up from the extracelluar environment. This uptake sustains the elevated levels of intracellular calcium [34] . Importantly, it has been shown that a CRAC channel inhibitor, GSK-7975A, inhibited the calcium entry into acinar cells.…”
Section: Effects Of Ethanol On the Cellular Mobilization Of Calcium Amentioning
confidence: 88%
“…These peripheral puncta correspond at the ultrastructural level to specialized regions of smooth ER positioned within 10 -20 nm of the plasma membrane, known as ER-PM junctions (Fig. 1B) Lur et al 2009;Orci et al 2009). In Jurkat T cells expressing ER-targeted horseradish peroxidase, electron microscopic studies show that native ER-PM junctions cover ,5% of the cell surface .…”
Section: The Molecular Choreography Of Socementioning
confidence: 99%
“…The molecular nature of these channels (Orai1) is now also known (15) and the link between Ca 2+ depletion of the ER and opening of the CRAC channels has been established: A reduction in the Ca 2+ concentration in the ER ([Ca 2+ ] ER ) causes translocation of a Ca 2+ -sensing protein, called STIM1, widely distributed in the ER membrane to so-called puncta in the ER close to the plasma membrane, where it can interact with and open Orai1 channels (16)(17)(18). This mechanism also operates in the pancreatic acinar cells, because stimulant-elicited release of Ca 2+ from the ER results in translocation of STIM1 to puncta close to the basolateral plasma membrane, specifically at locations where the ER is devoid of ribosomes and where interaction between STIM1 and Orai1 therefore occurs (19). Despite this, electrophysiological investigations of the currents evoked by Ca 2+ store depletion have so far failed to provide evidence for the existence in pancreatic acinar cells of Ca 2+ -selective currents of the CRAC type (20)(21)(22) originally discovered in mast cells (23), although activation of nonselective currents were shown (21,22).…”
mentioning
confidence: 99%
“…Despite this, electrophysiological investigations of the currents evoked by Ca 2+ store depletion have so far failed to provide evidence for the existence in pancreatic acinar cells of Ca 2+ -selective currents of the CRAC type (20)(21)(22) originally discovered in mast cells (23), although activation of nonselective currents were shown (21,22). Therefore, although the linkage between agonist-evoked Ca 2+ release from the ER and store-operated Ca 2+ entry, through STIM1 and Orai1, is established for the pancreatic acinar cells (19), there is uncertainty about the biophysical nature of the principal Ca 2+ entry channels. Endocytic Ca 2+ uptake (24) could also be important and does occur in pancreatic acinar cells (25).…”
mentioning
confidence: 99%